Genome-wide association study identifies five new schizophrenia loci - Ripke, Stephan; Rietschel, Marcella (Nature genetics, 2011)
The Schizophrenia Psychiatric Genome-Wide Association Study Consortium reports five genetic loci newly associated with risk of schizophrenia, involving 17,836 cases of schizophrenia and 33,859 healthy controls. The new locus with the strongest support of association was located within an intron for microRNA 137, a known regulator of neuronal development. Four other genome-wide significant loci for schizophrenia contain predicted targets of MIR137, suggesting that disruption to pathways involving MIR137 may be an etiologic mechanism in schizophrenia.